The Durrells of Corfu - Haag, Michael 1943- (London Profile Books, 2017)
The Durrell family are immortalized in Gerald Durrell's "My Family and Other Animals", but what of the real life Durrells? Why did they go to Corfu in the first place-- and what happened to them after they left? The real story of the Durrells is as surprising and fascinating as anything in Gerry's books, and Michael Haag, with his first hand knowledge of the family, is the ideal narrator, drawing on diaries, letters and unpublished autobiographical fragments. [This book] describes the family's upbringing in India and the crisis that brought them to England and then Greece. It recalls the genuine characters they encountered on Corfu-- Theodore the biologist, the taxi driver Spiro Halikiopoulos and the prisoner Kosti-- as well as the visit of American writer Henry Miller. And Haag has unearthed the story of how the Durrells left Corfu, including Margo's and Larry's last-minute escapes before the war. An extended epilogue looks at the emergence of Larry as a work famous novelist, and Gerry as a naturalist and champion of endangered species, as well as the lives of the rest of the family, their friends and other animals.
Includes bibliographical references and index.
Keywords: Durrell, Gerald, -- 1925-1995 -- Family; Dorrell family; Durrell, Gerald, -- 1925-1995 -- Homes and haunts -- Greece; Durrell, Lawrence -- Homes and haunts -- Greece; Dorrell family; Durrell, Gerald, -- 1925-1995; Durrell, Lawrence; Families -- Biography; Natural history -- Greece; Families; Homes; Natural history; Corfu Island (Greece); Greece -- Corfu Island; Family histories; Biographies; Biography; Family histories; Biographies